Lean Manufacturing for Financial Services - Soon, Sie Chye (2007)
In today's competitive environment, organizations struggle to find new ways to reduce cost while delivering high-quality service. This is particularly true for the financial services industry. Lean Manufacturing is a production optimization methodology that relentlessly seeks out and eliminate activities that do not create value for customers (i.e., waste). Its outcomes are characterized by production systems that